Recycling of Biomass Ashes 2011
DOI: 10.1007/978-3-642-19354-5_2
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fertilizing Effects of Biomass Ashes

Abstract: The reutilization of biomass ashes in agriculture is important to create nutrient cycles. In field and pot experiments we investigated the fertilizing effects of different biomass ashes (rape meal ash, straw ash, and cereal ash) for eight different crops on a loamy sand and a sandy loam. Special emphasis was given to phosphorus (P). The ashes showed large differences in their elemental composition. The highest P contents (10.5%) were measured in the cereal ash, and lowest in straw ash (1% P). The solubility of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
(23 reference statements)
1
17
1
1
Order By: Relevance
“…These problems aside, from the results presented here, it would not appear that wood ash and straw ash have great potential as P fertilisers, since the relative increase in biomass yield was not above 25 % in comparison to the HK Kalke and UCPH experiments showing yield increases of 50 % or more, even for sewage sludge ash. This result contradicted an earlier study in which a high P-fertilisation effect was found for rape meal, straw and cereal ashes [63]. However, as observed from the PCA plot, a small effect was observed on the plant elemental composition due to the wood ash and DKP treatments and greater effect of the straw ash treatment, but these differences were not clearly associated with differences in the aboveground biomass.…”
Section: Do the Different Recycled Fertiliser Products Tested Have Pocontrasting
confidence: 99%
“…These problems aside, from the results presented here, it would not appear that wood ash and straw ash have great potential as P fertilisers, since the relative increase in biomass yield was not above 25 % in comparison to the HK Kalke and UCPH experiments showing yield increases of 50 % or more, even for sewage sludge ash. This result contradicted an earlier study in which a high P-fertilisation effect was found for rape meal, straw and cereal ashes [63]. However, as observed from the PCA plot, a small effect was observed on the plant elemental composition due to the wood ash and DKP treatments and greater effect of the straw ash treatment, but these differences were not clearly associated with differences in the aboveground biomass.…”
Section: Do the Different Recycled Fertiliser Products Tested Have Pocontrasting
confidence: 99%
“…However, the results of the present study suggest that the method is not suitable for predicting the amount of plant-available P in waste materials. Schiemenz et al (2011) recommend extracting biomass ash with citric acid, which dissolves around 80% of ash-P, for prediction of the P fertilisation effect.…”
Section: P Fertilisation Effects Of Mbm and Bwamentioning
confidence: 99%
“…This was attributed to the low availability of P within ash as identified by Khanna et al (1994). Through dissolution tests with different ash/ water ratios, Khanna et al (1994) observed the rapid dissolution of K, Ca and Mg, and the comparative insolubility of P. In addition, an increased soil pH following the addition of ash may have further reduced the solubility and availability of P in soil (Demetz and Insam, 1999;Schiemenz et al, 2011), and precipitation of phosphate ions with Fe and Al can form insoluble compounds, lowering the H 2 PO 4 content taken up by plants (Omil et al, 2011). The increase in pH of the digestate following mixing with ash may also result in the gaseous loss of ammonia (Bougnom et al, 2012).…”
Section: Acidificationmentioning
confidence: 90%
“…Ash provides a source of micronutrients (Demeyer et al, 2001;Kuba et al, 2008;Odlare and Pell, 2009;Schiemenz et al, 2011). Primary production Gross primary productivity (GPP) measures the rate of solar energy conversion into biomass.…”
Section: Nutrient Cyclingmentioning
confidence: 99%